Challenges, obstacles and strategies in dental scientific production in Guerrero, Mexico: an exploratory qualitative analysis - Juárez-Medel, Carlos Alberto (2025)
Objective: To explore the experiences of researchers and dental professionals in the State of Guerrero, Mexico, with the aim of identifying the main challenges, barriers, and strategies in scientific production. Materials and methods: An exploratory qualitative study was conducted using thematic coding of narratives collected through an online form. Using purposive sampling, 14 dental professionals—with and without research experience—were recruited from educational and healthcare institutions in Guerrero, Mexico. The initial coding was performed using Atlas.ti V23.2.1®. Results: The main barriers identified were lack of financial resources, limited institutional support, and difficulties in publishing, while the proposed measures included greater access to funding, research training, and the consolidation of academic networks. In addition, the experiences highlighted persistence, mentorship, and collaboration as key elements in research development. Conclusions: The analysis highlights the need to strengthen support for dental research through institutional and governmental policies that promote scientific production and its integration into the academic community.